20th Century French Fashion Design (Journal of Pharmaceutical Negative Results, 2023)
In the article, the authors talk about the leading fashion designers of France, analyze their life and work and compare them with each other. It explores the reasons why each fashion designer is unique and inimitable. The authors also analyze the influence of France fashion designers on other European countries and world fashion design in general. The article describes the success of France fashion designers not only due to sketches, but also about the quality of fabrics, the support of famous people, especially stars, and healthy competition. In the article, the authors talk about the support of one fashion designer to another, the exchange of experience and the positive effect of healthy criticism on creativity. Each fashion designer mentioned in the article wrote their names in the history of art with golden letters due to their hard work and talents. Their creativity and life experience can be a great example for every young designer.